2012
DOI: 10.2147/ijn.s34530
|View full text |Cite
|
Sign up to set email alerts
|

Wound-healing effect of micronized sacchachitin (mSC) nanogel on corneal epithelium

Abstract: Abstract:The extraction residue of the Ganoderma fruiting body, named sacchachitin, has been demonstrated to have the potential to enhance cutaneous wound healing by inducing cell proliferation. In this study, a nanogel formed from micronized sacchachitin (mSC) was investigated for the potential treatment of superficial chemical corneal burns. Reportedly, mSC has been produced successfully and its chemical properties confirmed, and physical and rheological properties characterized. An in vitro cell proliferati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…This indicated that those short fibers of mSC was so small in both length and diameter that they could be hydrated to become nanogel when mSC was dispersed in aqueous medium. Rheological characteristics of m SC nanogel have also been reported by Chen et al [ 29 ]. Please also see Additional file 1 for details.…”
Section: Resultssupporting
confidence: 64%
See 3 more Smart Citations
“…This indicated that those short fibers of mSC was so small in both length and diameter that they could be hydrated to become nanogel when mSC was dispersed in aqueous medium. Rheological characteristics of m SC nanogel have also been reported by Chen et al [ 29 ]. Please also see Additional file 1 for details.…”
Section: Resultssupporting
confidence: 64%
“…Physical characteristics of m SC have been reported by Chen et al [ 29 ]. It was summarized as the following.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…In a following study (Su et al, 2005 ), the Sacchachitin membranes appeared to boost keratinocytes proliferation and prevent metalloproteinase-related ECM degradation, contributing to accelerate the healing process of a chronic wound in vivo model. Furthermore, a micronized Sacchachitin nanogel has been investigated to treat superficial chemical corneal burns in vivo (Chen et al, 2012 ), while the anti-oxidant and immuno-modulating effects of extracts from mycelia of some medicinal fungi have been investigated for skin aging (Kim et al, 2014 ), dermatitis (Hwang et al, 2012 ), and UV-protection (Nanbu et al, 2011 ; Bae et al, 2012 ), suggesting a promising mycelia biological value yet unexplored.…”
Section: Self-growing Mycelium-based Biomaterialsmentioning
confidence: 99%